ANALISIS BIAYA DAN PENDAPATAN USAHATANI SAYURAN DI KECAMATAN RATU AGUNG KOTA BENGKULU - Rita Feni; Fithri Mufriantie; Edy Marwan; Yayang Fitriani (Agribusiness Study Program Universitas Sriwijaya in Collaboration with Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2017)
This study aimed to analyze cost and revenue of vegetable farm in Ratu Agung district Bengkulu city. Location determined purposively with criteria as vegetable production center in Bengkulu city. Bengkulu city has potency for vegetable farm that can be grown in lowland and not needing a large area. Vegetable dominantly planted is water spinach, collards, and spinach. Method used in this study is survey method. Sample determined in this study by proportional random sampling. Data used in this study were primary and secondary. The study result shows that vegetable farm in RatuAgung district Bengkulu city can be developed as consumer needs provider of vegetables in Bengkulu city where R/C score of the three vegetables are >1. BEP score of production volume and price BEP has passed the break even point, only B/C ratio for spinach scored less than one.